Deadly triangle: honey bees, mites, and viruses - Lamas, Zachary S.; Evans, Jay D. (Frontiers in Bee Science, 2024)
Honey bees are managed by humans on all continents except Antarctica, leading to an exceptional database of colony growth and survival. Honey bee colony losses in the United States are approximately 50% annually, and losses in other countries range from 10% to 60%. These losses reflect chemical, climatic, and nutritional stresses alongside immense pressure from diverse parasites and pathogens. The combination of RNA viruses and parasitic mites that vector these viruses plays a primary role in colony losses. Here, we discuss virus infection with and without mite vectors, bee defenses, colony vulnerabilities, and the roles of managed beekeeping in mitigating and aggravating the impacts of Varroa mites and viral disease.